Pengaruh Artificial Intelegence (AI) Terhadap Kemampuan Berfikir Kristis Matematis Siswa - Ratnasari Ratnasari; Mewa Zabeta; Faza Zikri Sholeha (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
With the advancement of technology and computing capabilities of computers, various applications and algorithms that were previously not applicable to portable devices such as laptops and smartphones can now be applied. Artificial intelligence (AI) is one of the increasingly popular techniques that are now a part of everyday life. AI is an umbrella term that refers to the simulation of human intelligence by machines that use big data to perform various tasks. AI has benefited many aspects of human life, including education. However, AI also has significant negative effects. This study aims to study the influence of artificial intelligence on students' critical thinking skills. This study uses qualitative research and literature analysis. However, the study also identified several negative impacts, including reliance on technology, unassured information quality, social isolation, and ethical and privacy concerns. Therefore, a balanced and strategic approach is needed in integrating AI in education to ensure that its benefits can be maximized, while its negative impact is minimized.